Interaction of desialated guinea pig erythrocytes with the classical and alternative pathways of guinea pig complement in vivo and in vitro. - Brown, E J (1983)
We examined the fate of desialated autologous erythrocytes injected intravenously into guinea pigs (GP). Desialated GP erythrocytes (E) were lysed directly or cleared by the reticuloendothelial system in normal GP (NIH-GP) and cleared by the reticuloendothelial system in GP genetically deficient in the classical complement pathway component C4 (C4D-GP), which activate complement only via the alternative pathway. Desialated E were also cleared in cobra venom factor-treated GP (CVF-GP), which had less than 1% of normal C3 levels, but were not cleared at all in C4D-CVF-GP. Preinjection of asialoorosomucoid (ASOR) and ovalbumin (OVA) had no effect on the rate of E clearance. These in vivo studies indicated that complement activation is essential for clearance of desialated E and that clearance is unaffected by blockade of galactose or mannose receptors. Inhibition of complement-mediated clearance required blockade of both classical and alternative complement pathways. In vitro studies showed that lysis of desialated E could occur in NIH-GP serum (GPS) but not in C4D-GPS. Surprisingly, CVF-GPS also caused lysis of desialated E. Lysis was dependent on both natural antibody to desialated E and classical pathway activation; natural antibody was of both the IgG and IgM classes. C3 uptake studies demonstrated that almost 10 times as many C3 molecules/E were deposited by NIH-GPS as by C4D-GPS or CVF-GPS onto desialated E. Approximately equal numbers of C3 molecules were deposited by CVF-GPS, which did lyse desialated E, and by C4D-GPS, which did not. We suggest that the molecular mechanism of in vivo clearance and in vitro lysis of desialated E by CVF-GP is via classical pathway deposition of C3b into sites on the erythrocyte surface protected from inactivation by H (beta 1H) and I (C4b/3b inactivator). Deposition of C3b into these sites by alternative pathway activation is sufficient to cause clearance but not lysis of desialated E. CVF-GPS may not represent an adequate reagent for testing the complement dependence of various biologic phenomena, particularly if the question involves surfaces that can provide protected sites for C3b molecules.